The effect of the school environment on the provision of quality education: a study of schools in Mogadishu, Somalia - Idris, Mohamed Osman Abdi; Omar, Abukar Mukhtar; Mohamed, Mohamed Jama; Hussein, Abdikadir Abdulahi; Mohamed, Mohamedamin Moallin Omar (Frontiers in Education, 2025)
This study investigates the impact of the school environment, specifically school physical infrastructure (SPI) and school management and leadership (SML), on the provision of quality education (QE) in Mogadishu, Somalia. Guided by the Educational Effectiveness Theory, the research examines the interconnected roles of SPI and SML in fostering an educational framework conducive to academic achievement. A quantitative research design was employed, involving surveys of 238 respondents from secondary schools in Mogadishu, including school principals, teachers, and parents. The study utilized SPSS and R for data analysis, including measurement modeling, reliability testing, and path analysis. The findings reveal that both SPI and SML significantly influence QE, with SPI exerting a stronger impact (β = 0.491, p = 0.000) compared to SML (β = 0.350, p = 0.000). Adequate infrastructure—spanning classrooms, libraries, and laboratories—directly enhances students’ learning experiences and academic performance. Simultaneously, effective leadership practices, such as strategic decision-making and resource allocation, foster collaborative school cultures that support educational excellence. Structural models confirmed the reliability and validity of these constructs while underscoring their distinct yet interrelated roles. The study highlights the challenges faced by schools in Mogadishu, including inadequate infrastructure and weak leadership, and proposes targeted recommendations. These include investments in physical infrastructure, capacity-building for school leaders, community collaboration, equity promotion, monitoring mechanisms, and teacher development programs. By addressing these areas, stakeholders can create a holistic and sustainable framework for improving educational quality in Mogadishu.